Society and Politics in the Caribbean - Clarke, Colin G. author. aut Link
XVI, 295 p.
Keywords: A study of the relationship between society and politics in the Caribbean, this book examines the importance of democracy to these subjects. It argues that despite structural differences, these ex-colonies gravitate toward democratic values and practices because of European colonization.